Whistle blower in Malaysia: an appraisal of the law in the light of the whistleblower protection act 2010 / Muhammad Afif Hamzah ...[et al.] - Hamzah, Muhammad Afif; Mohd Jamil, Maznee; Md Zin, Norlia; Ibrahim, Noraini (2011)
The purpose of this research is to examine the extent of protection conferred under the Companies Act 1965, Capital Market Services Act 2007, Industrial Relations Act 1967, Occupational Safety and Health Act 1994 and the Whistleblower Protection Act 2010 in relation to whistleblowing. This is done with the objective of identifying the sufficiency of protection prior to the enactment of the Whistleblower Protection Act 2010 and whether the Whistleblowing Act 2010 has addressed any shortcomings. To enable us to obtain better understanding of the law on whistleblowing, we have employed qualitative methods whereby questions were designed and interviews were conducted with relevant government bodies. The conclusion that we can draw from the research is that the recently enacted Whistleblowing Protection Act 2010 has addressed some of the shortcomings faced by other abovementioned statutes. However, in order to improve whistleblowing protection, several more reforms is proposed in this Research to be made under the Whistleblowing Protection Act 2010.